Impact of competitions for ideas and business plans on firm creation and development of entrepreneurial university: case study of the IPC in Portugal - Jo\~ao P. C. Marques (Triple Helix, 2016)
The phenomenon of the entrepreneurial university has received considerable attention in recent decades, since the entrepreneurial orientation of academia could put regions and nations at an advantage in areas of economic activity where the focus is on emerging knowledge. Empirical research on entrepreneurial initiative incentives within universities and involving students and lecturers is scarce. This article examines the impact of competitions for ideas and business plans on start-up creation and patent registration, given the involvement of lecturers, the existence of R&D underpinning the idea and the technological area. The data used refer to 20 business ideas finalists in competitions between 2008 and 2014 at the Polytechnic Institute of Coimbra. The results show that these incentives have a significant impact on firm creation and patent registration and that the ideas and business plans competitions are important instruments to encourage the entrepreneurial spirit in an academic environment, motivating students and lecturers.
Keywords: L26; M13; 330; Triple helix; Entrepreneurial universities; Entrepreneurship; Firm creation